PRognostic and predictive potential Of multiparametric dynamic whole-body 18F-FDG PET Imaging using a Long axial field-of-view (LAFOV) system for FIRST-line chemo-immunotherapy efficacy in advanced non-small cell lung cancer: PROFIL-1 study protocol - Margaux Geier; Karim Amrane; David Bourhis; Pierre-Yves Le Roux; Jessica Nguyen; Estelle Dhamelincourt; Renaud Descourt; Gilles Quéré; Marie Guegan; Benjamin Besse; Désirée Déandreis; Florent Besson; et al. (PLoS ONE, 2026)
Background Revolution of chemo-immunotherapy (CT-IO) in the first-line treatment of metastatic non-small-cell lung cancers (NSCLC) without actionable genomic alterations (AGAs) has dramatically improved prognosis, providing long response in a subset of patients. Due to the highly heterogeneous nature of the disease, most of patients do not show long term benefit. Long axial field of view positron emission tomography (LAFOV-PET) scanner is a new emerging system allowing dynamic whole-body imaging with higher sensitivity, representing unique opportunity for oncological applications. The aim of this study is to determine whether 18 F-fluorodeoxyglucose positron emission ( 18 F-FDG) LAFOV-PET derived parameters might have prognostic and predictive potential for CT-IO outcomes in NSCLC. Methods PROFIL-1 (NCT06738680) is a multicentre, prospective single-arm biomarker pilot study investigating the prognostic and predictive potential of multiparametric 18 F-FDG LAFOV-PET for first-line CT-IO efficacy in advanced NSCLC, with a planned enrolment of 120 patients at 2 French sites. Adult patients with treatment-naïve advanced non-squamous or squamous NSCLC without AGAs and eligible for first-line CT-IO will be recruited for PROFIL-1. Patients will undergo baseline LAFOV-PET before treatment (optional second dynamic LAFOV-PET after CT-IO induction). The primary objective is to evaluate the prognostic and predictive potential of a whole-body multiparametric analysis (radiomics and dynamics) derived from LAFOV-PET for first-line CT-IO efficacy, using the rate of disease progression or death at one year as the primary endpoint, assessed by investigators according to RECIST v1.1 criteria. Secondary endpoints included correlations between imaging parameters and clinico-pathological characteristics, comparison between direct Patlak and indirect Patlak reconstruction methods to determine dynamic parameters such as Ki (the net influx rate) and distribution volume (DV), number of detected tumor lesions and signal-to-noise ratio (vs. SAFOV-like imaging), objective response rate, overall survival and safety. The study opened for enrolment in January 2025. Duration of inclusions: 2 years. Clinical trial information NCT06738680.